(NpTICELOW (B:s (NSBORNIK (B: (NPEREWOD S ITALXQNSKOGO (B/s - (NgU\RRA(B, (NtONINO(B,s; (NwER[ININA(B, (Nl(B.,s; (NzASLAWSKAQ(B, (Ni(B.,s ((NmOSKWA (B:s (NrADUGA(B,s, 1985)
(NdO ZB)QÆRKI WKL@^ENÆ ROMANI (B"(NpARALELXNA L@DINA(B" Æ "(NzGRAQ PTAHÆW(B", (NPOWÆSTX (B"(NaMARKORD(B", (NP(B'Ã(NSA (B"(NwDOWA(B", (NKÆNOSCENARÆJ (B"æ (NPLIWE KORABELX(B", (NOPOWÆDANNQ TA LÆRI^NA POEMA (B"(NmED(B".s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- )Qæ(NTALÆJSXKA LÆTERATURAs)E -- (NpOW)QÆSTÆs)E -- (Np(B')QÃ(NSIs)E -- )Qæ(NTALÆQs)E